Emerging Nutritional and Climate-resilient Strategies in Mulberry for Enhanced Cocoon Quality in Sericulture - , Kruthika M S, Rakshitha K R, N M Praveen Kumar Gowda, Bhuvaneshwar Rajesh Naik, Pritish Chavan (Archives of Current Research International, 2025)
Sericulture relies fundamentally on the nutritional quality of mulberry (Morus spp.) leaves, the exclusive feed for the silkworm, Bombyx mori L. In recent years, efforts have intensified to improve cocoon yield and silk quality through strategic nutritional enrichment of mulberry foliage and the adoption of climate‑resilient cultivation practices. This review outlines how integrating soil and foliar nutrient supplementation particularly with elements like nitrogen, zinc, and iron alongside organic amendments and microbial inoculants such as plant growth‑promoting rhizobacteria (PGPR) and mycorrhizal fungi, can significantly enhance leaf quality. Improved leaf nutrition directly benefits key cocoon characteristics, including larval growth, cocoon weight, shell percentage, filament length, and feed utilization efficiency. Moreover, cultivation techniques tailored to mitigate climatic stresses such as the use of drought‑tolerant mulberry genotypes, mulching, and efficient irrigation systems help maintain consistent leaf yield and quality. By combining targeted nutrient strategies with climate‑smart agronomic practices, sericulture can achieve higher productivity and superior cocoon traits while reducing dependence on synthetic inputs, lowering production costs, conserving natural resources, and minimizing environmental impact thereby aligning silk production with long‑term economic viability and ecological sustainability.